Teledentistry Through Web Apps And IODT - Reforming Dental Care In The Covid-19 Era: UPGRADING TELEDENTISTRY TO THE CHALLENGE - JHA, KUNAL; Mandal, Yagnaseni; J, Avinash; KUMAR, GUNJAN; S, vinay; Singh, Arpita (Internet of Things and Artificial Intelligence Journal, 2021)
Health care affordability, accessibility, availability, and quality have long been a major concern for humanity. It is the use of telecommunications and information technology for consultations, education, and public awareness, with the goal of improving patient care and time management. Teledentistry is a form of telemedicine that is used in the field of dentistry. It is beneficial in improving services to underserved people, such as those in rural or less developed areas. The recent spread of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and its associated coronavirus disease (COVID-19) has caused widespread public health concerns However, due to restrictions in movement, it was difficult for the patients to visit the clinics for routine check-ups. This was overcome by the advancements in technology like the introduction of the INTERNET OF DENTAL THINGS(IODT) which has a major impact on and has tremendously transformed teledentistry. Dental health app platforms using AI have made teledentistry more accessible and user-friendly. The advent of sensor and camera technologies has opened up new possibilities and breakthroughs. Furthermore, teledentistry can be a beneficial tool for peer education, consultations, and ensuring proper referral channelizing.